Implementing sustainable halal-green frameworks: An analysis of waste valorization and ethical consumption in institutional canteens - Arizal Permana Aqila; Siska Wahyuningsih; Ika Feni Setyaningrum (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: Halal green business is a business model that integrates environmental sustainability with Islamic ethical values in its operations. Tinuku Mart, as an Islamic-based campus canteen, implements this concept through a waste sorting system according to its type, both organic and inorganic, and actively campaigns for a minimal waste movement in the canteen environment by encouraging the reduction of single-use packaging and providing supporting facilities for waste management. This study aims to examine the application of waste management at Tinuku Mart as part of a halal-based green business practice. Methods: The collected data underwent a systematic analysis process involving data reduction, narrative and descriptive presentation, and interpretive conclusion-drawing to link waste management practices with halal and sustainability values. Finding: The findings indicate that waste sorting has a positive impact on environmental cleanliness, waste management efficiency, and the awareness of the academic community regarding sustainability. In addition, halal principles are reflected in the provision of thayyib, ethical, and hygienic food. Conclusion: This study shows that Tinuku Mart successfully presents a sustainable business model that aligns with the context of a modern Islamic campus and supports environmentally conscious development. Novelty/Originality of this article: This research offers a unique perspective by merging the concept of thayyib (quality and ethics) with modern circular economy practices within a higher education setting.